The The Social Dynamics of Student Brawls: A Theoretical Review of Causes, Impacts, and Interventions - Edwin; Suma Ketut; Candiasa I Made; Jampel I Nyoman (South Sulawesi Education Development (SSED), 2026)
Student brawls reflect the complex social dynamics of adolescence and pose a critical challenge within the educational environment. This study employs a Systematic Literature Review (SLR) to investigate the root causes, consequences, and intervention strategies related to student brawls. A thorough search of Scopus and Dimensions databases was conducted, focusing on publications from 2015 to 2025. Inclusion criteria required that studies be published in educational journals, explicitly address student brawls, and be available in full-text form in English. Data were extracted using a standardized form and analysed thematically, drawing on social control theory and social learning theory. The findings reveal that internal factors—such as identity crises and emotional instability—and external factors—like peer pressure, lack of family support, repressive school policies, and negative influences from social media—are primary contributors to student brawls. These acts result not only in physical harm but also in psychosocial trauma and disruption of the educational environment. Effective interventions require a holistic and preventive approach, including character education, family counselling, and the development of a supportive school climate. This study highlights the urgent need for integrated, humanistic strategies to cultivate a culture of peace in schools and address the structural roots of youth brawls.